Prehospital Pediatric Respiratory Distress and Airway Management Training and Education: An NAEMSP Position Statement and Resource Document. (4th January 2022) - Lyng, John; Harris, Matthew; Mandt, Maria; Moore, Brian; Gross, Toni; Gausche-Hill, Marianne; Donofrio-Odmann, J. Joelle
Abstract: Although pediatric airway and respiratory emergencies represent high-acuity situations, the ability of EMS clinicians to effectively manage these patients is hampered by infrequent clinical exposure and shortcomings in pediatric-specific education. Cognitive gaps in EMS clinicians' understanding of the differences between pediatric and adult airway anatomy and respiratory physiology and pathology, variability in the training provided to EMS clinicians, and decay of the psychomotor skills necessary to safely and effectively manage pediatric patients experiencing respiratory emergencies collectively pose significant threats to the quality and safety of care delivered to pediatric patients. NAEMSP recommends: Pediatric airway education should include discussion of the factors that make pediatric airway management challenging. EMS agencies should provide pediatric-specific education that addresses recognition and treatment of pediatric respiratory distress based upon pathophysiology affecting upper airways, lower airways, cardiovascular systems, or extrinsic causes of disordered breathing. Pediatric airway training should also differentiate between hypoxic and hypercapnic respiratory failure. Education should emphasize that the cognitive and psychomotor skills requisite in management of pediatric respiratory emergencies will differ across patient age groups. EMS clinicians should be provided education and training in technology-dependent children and children and youth with special health care needs. EMS clinicians should receive initial and ongoing education and training in pediatric airway and respiratory conditions that emphasizes the principle of using the least invasive most effective strategies to achieve oxygenation and ventilation. Initial and continuing pediatric-focused education should be structured to maintain EMS clinician competency in the assessment and management of pediatric airway and respiratory emergencies and should be provided on a recurring basis to mitigate the decay of EMS clinicians' knowledge and skills that occurs due to infrequent field-based clinical exposure. Integration of clinician education programs with quality management programs is essential for the development and delivery of initial and continuing education intended to help EMS clinicians attain and maintain proficiency in pediatric airway and respiratory management.